When Abused Women Get Away with Murder: Law, Justice and Truth in three English-language Malaysian Novels by Women - Eng, Malaysia, Chuah Guat (Asiatic: IIUM Journal of English Language and Literature, 2013)
Although the socially oppressed woman is almost a standard feature in Malaysian English-language fictional narratives, abused-women-turned-murderers are found only in novels by women. Between 1994 and 2000, three women published novels featuring women who kill and confess their crimes but, notably, are not brought to justice. To date, these are the only Malaysian examples of this sub-genre of the crime novel. This paper examines the moral universes depicted in the three novels, and identifies culturally and institutionally determined concepts and perceptions of law, justice and truth that might explain why the women who kill are allowed to go unpunished.